GE_GERICHTE P/8970/2021 vom 16. November 2021 - GE Cour de justice (2021)
CLASSEMENT DE LA PROCÉDURE;DÉNONCIATION CALOMNIEUSE;CONTRAINTE(DROIT PÉNAL);OBLIGATION D'ENTRETIEN | CPP.319.al1.letb; CP.303; CP.181; CP.217